Analisis Penerapan Sistem Akuntansi pada Usaha Kecil Menengah di Kota Lamongan (Studi Kasus pada Depot Air Minum Wijaya) - Opi Trimarita Widiyanti; Amin Sadiqin; Taufik Kurniawan (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This research aims to analyze the application of accounting systems in small and medium enterprises (UKM) in Lamongan City, with a case study at the Wijaya Drinking Water Depot. SMEs play an important role in the regional economy, but often do not implement an adequate accounting system in managing their finances. This research uses a descriptive qualitative method with a case study approach. Data was obtained through observation, interviews and documentation. The research results show that the implementation of the accounting system at the Wijaya Drinking Water Depot is still simple and does not fully meet applicable accounting standards. However, implementing the system has helped owners make better business decisions. This research suggests increasing the use of accounting technology for efficiency and accuracy in financial management in SMEs.